Transfer learning for natural language processing. (Manning Publications, 2022)
Paul Azunre uses Kaggle kernels to experiment with some key NLP architectures, like BERT, GPT etc to generate some text, perform some classification, etc. Time permitting. He also discusses some major advances in NLP since his book "Transfer Learning for NLP" was published (August 2021).